(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From the genus Pantecphylus Karsch (Orthopteroidea, Ensifera, Tettigonoidea, Pseudophyllidae), two males collected in the province Kassai last century, were found among the material preserved in the African Museum Tervuren (Belgium). Their genitalia showed different structures, not found in males of the genus studied before. Two new species were created, named P. lueboensis sp. n. and P. konduensis sp. n.. Conspecific females were not available. Including the new species, 16 species of the genus Pantecphylus were tabled.